Application of biological products in arabica coffee (Research, Society and Development, 2022)
The coffee industry is prominent in the Brazilian economy and the estimated production area in 2022 was 1,431,018.0 ha, with productivity around 27 bags per hectare, and the expected production reaching 39 million bags. However, as it is a perennial crop, it needs attention in the deployment, and new techniques and/or products to ensure the quality of seedlings for transplanting to have good performance and development. A new option to help the development of coffee trees is the use of microorganisms as plant growth promoters. Thus, the objective of this research is to evaluate the effect of different biological products used in the initial growth of the coffee tree. The research was conducted from February to November 2022, in the city of Machado, Minas Gerais, using Arabica coffee IAC-144 seedlings. For planting, pots with a capacity of 5 kg containing formulated substrate were used. The experiment used a randomized block design with four treatments. After 120 days, the characteristics of the coffee plants were evaluated and then the data were tabulated and submitted to variance analysis. The use of microorganisms demonstrated greater vegetative development of the coffee trees, the use of Azospirillum brasiliense presented the highest mean values for height, number of leaves and stem diameter. It is concluded that the use of microorganisms provides a gain in the vegetative growth of coffee trees, producing more vigorous plants in the first stages of implementation of the coffee plantation.